This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Put t = r = 1 ∏ n ( x + r ) , this will give d t = ( r = 1 ∏ n ( x + r ) ) ( r = 1 ∑ n x + r 1 ) .
So basically the entire expression is substituted giving I = ∫ d t = t + C . This on putting the limits after substituting back x we get , I = ( n + 1 ) ! − n ! = n . n ! and that gives the answer.